Biotransformation of ferulic acid by the phytopathogenic fungi Colletotrichum acutatum and Lasiodiplodia theobromae (2016)
The microbial transformation of ferulic acid (FA) offers a cleaner, more economical alternative for the natural production of flavorings and fragrances. In the present study, the biotransformation of FA using the filamentous phytopathogenic fungi Colletotrichum acutatum and Lasiodiplodia theobromae was researched. Initially, the toxicity of FA against both fungi was evaluated; the FA displayed a moderate toxicity (total inhibition at concentrations ≥ 2000 mg L-1) and apparently a detoxification mechanism was present. Afterwards, the microorganisms were incubated with the substrate at room conditions using a Czapek-Dox culture medium. The results demonstrated that the FA was mainly converted to 4-vinylguaiacol, reaching the highest abundance within the first 48 hours. To a lesser extent, acetovanillone, ethylguaiacol, and vanillin, among others, were produced. Interestingly, the compounds generated in the biotransformation of FA with C. acutatum and L. theobromae have been used as flavorings. Based on the identified metabolites, a possible metabolic pathway was proposed.